Inhibition of the JAK-STAT3 Signaling Pathway by Ganoderic Acid A Enhances Chemosensitivity of HepG2 Cells to Cisplatin - Yao, Xiangyang; Li, Guilan; Xu, Hui; Lü, Chaotian (Planta Medica, 2012)
Ganoderic acid A is a lanostane triterpene isolated from Ganoderma lucidum. It has been reported to exhibit antitumor activity, which is mainly mediated through its inhibitory effect on nuclear transcription factor-kappaB and activator protein-1. But the role of ganoderic acid A in JAK-STAT3 signaling pathways is still unclear. In the present study, we investigated the effect of ganoderic acid A on the signal transducer and activator of the transcription 3 pathway and evaluated whether suppression of the signal transducer and activator of transcription 3 activity by ganoderic acid A could sensitize HepG2 cells to cisplatin. Our results show that ganoderic acid A significantly suppressed both the constitutively activated and IL-6-induced signal transducer and activator of transcription 3 phosphorylation in HepG2 cells. Inhibition of the signal transducer and activator of transcription 3 tyrosine phosphorylation was found to be achieved through suppression of JAK1 and JAK2. Furthermore, ganoderic acid A promoted cisplatin-induced cell death by enhancing the sensitivity of HepG2 cells to cisplatin mainly via the signal transducer and activator of transcription 3 suppression. These observations suggest a potential therapeutic strategy of using ganoderic acid A in combination with chemotherapeutic agents for cancer treatment.
Keywords: ganoderic acid A; STAT3; chemosensitivity; cisplatin; Ganoderma lucidum; Aphyllophoromycetideae